Advances in micro-/nanorobots for cancer diagnosis and treatment: propulsion mechanisms, early detection, and cancer therapy - Baiyang Fu; Dan Luo; Chao Li; Yiwen Feng; Wenlong Liang (Frontiers in Chemistry)
In recent years, medical micro-/nanorobots (MNRs) have emerged as a promising technology for diagnosing and treating malignant tumors. MNRs enable precise, targeted actions at the cellular level, addressing several limitations of conventional cancer diagnosis and treatment, such as insufficient early diagnosis, nonspecific drug delivery, and chemoresistance. This review provides an in-depth discussion of the propulsion mechanisms of MNRs, including chemical fuels, external fields (light, ultrasound, magnetism), biological propulsion, and hybrid methods, highlighting their respective advantages and limitations. Additionally, we discuss novel approaches for tumor diagnosis, precision surgery, and drug delivery, emphasizing their potential clinical applications. Despite significant advancements, challenges such as biocompatibility, propulsion efficiency, and clinical translation persist. This review examines the current state of MNR applications and outlines future directions for their development, with the aim of enhancing their diagnostic and therapeutic efficacy and facilitating their integration into clinical practice.